Open access availability of anatomy papers presented at meetings of the American and British Associations of Clinical Anatomists. Issue 5 (6th March 2020) - Miller, George W.; Stoner, Rebecca; Boissaud‐Cooke, Matthew A.; Lim, Joseph; Furness, Hugh; Putt, Oliver; Lewis, Thomas L.
Abstract: Introduction: Dissemination of research depends on published work being accessible. In many disciplines open access (OA) research is more frequently cited, although this has never before been demonstrated amongst anatomy publications. The objective of this study was to assess a selection of published anatomy papers to determine the effect of gold and bronze OA availability on citation rates. Materials and Methods: Taken together, 625 peer‐reviewed publications were identified from 2927 abstracts presented at meetings of AACA (2003–2010) and BACA (2000–2015). Results: In total 18.75% (69 of 368) of papers presented at BACA and 21.79% (56 of 257) of those presented at AACA reached OA publication.  Citation rates are significantly higher amongst OA papers as compared to non‐OA papers presented at these two anatomy conferences (OA 18.95, Non‐OA 15.14 p = 0.047). OA papers were most commonly themed around education and pure anatomy. Conclusions: The average OA publication rate of 20.0% in anatomical research arising from these conferences is significantly lower than the average rate for scientific research. Citation rates are significantly higher amongst OA anatomy papers presented at these two conferences.